Understanding the drivers of academic achievement: Evidence for Portugal’s high school system, a machine learning approach - Mendes, Ricardo António Dias Costa Carvalho (2022)
A thesis submitted in partial fulfillment of the requirements for the degree of Doctor in Information Management, specialization in Information and Decision Systems